2020
DOI: 10.1016/j.jvs.2020.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Prospective Randomized Trial of Negative Pressure Wound Therapy for Infrainguinal Revascularization Groin Incisions

Abstract: The VSG CRI score was not different between high-use (EVR, 5.5 6 2.1; OPEN, 5.0 6 2.0) and low-use centers (EVR, 5.5 6 2.1; OPEN, 4.9 6 2.0).Conclusions: Stress test utilization before AAA repair varies widely despite similar patient risk profiles. There was no observed reduction in MACE or 1-year mortality among high stress test-using centers. The value of routine stress testing before AAA repair should be reconsidered and used on a more judicious basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…The included studies represent a global surgical patient population with 7451 patients receiving ciNPT and 16,085 patients receiving SOC across 16 countries. 11–16,20–97 The countries represented included the USA (n = 42), Germany (n = 11), Australia (n = 6), Canada (n = 5), Italy (n = 4), Spain (n = 3), the UK (n = 3), Denmark (n = 2), and one each from Austria, Brazil, France, Ireland, the Netherlands, South Africa, Taiwan, and Turkey. Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies represent a global surgical patient population with 7451 patients receiving ciNPT and 16,085 patients receiving SOC across 16 countries. 11–16,20–97 The countries represented included the USA (n = 42), Germany (n = 11), Australia (n = 6), Canada (n = 5), Italy (n = 4), Spain (n = 3), the UK (n = 3), Denmark (n = 2), and one each from Austria, Brazil, France, Ireland, the Netherlands, South Africa, Taiwan, and Turkey. Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings.…”
Section: Resultsmentioning
confidence: 99%
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the 26 RCTs 25–50 and their included patients is summarized in the Table in Supplemental Digital Content 3, http://links.lww.com/SLA/E499. Their median publication date was 2010 (interquartile range=23; range=1981–2021).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies had an unclear 30,39,41,44,46,48 risk of bias, and 9 studies had a high 26,28,29,31,33,36,38,40,47 risk of bias regarding allocation concealment. Researchers and participants were not blinded to treatment allocation in 12 studies 25,26,28–31,33,36–38,47,49 . In 5 studies, 39–41,44,48 it was unclear whether researchers and participants were blinded to treatment allocation.…”
Section: Resultsmentioning
confidence: 99%